The Effect of Oral Polyethylene Microplastic Doses on Femoral Bone Cell Profiles in Wistar Rats - Nixon Adrian Wijaya; Yudhiakuari Sincihu; Henry Ricardo Handoyo; Taufin Warindra; Inge Wattimena (ECOTON: Ecological Observation and Wetlands Conservation, 2026)
Microplastics pose a potential health risk because they can enter the body orally and accumulate in various organs, including bone, potentially disrupting bone homeostasis through oxidative stress and inflammation. This study aimed to analyze the effect of oral polyethylene microplastic exposure on the femoral bone cell profile of Wistar strain Rattus norvegicus. A laboratory experimental study with a post-test only control group design was conducted using 28 male Wistar rats divided into four groups: control (X0) and treatment groups receiving LDPE microplastics (≤20 µm) at doses of 1.25 mg/day (X1), 2.5 mg/day (X2), and 5 mg/day (X3) for 28 days. Femoral bones were examined histologically using HE staining, and osteocytes, osteoblasts, and osteoclasts were counted. Results showed a significant increase in osteocyte and osteoclast numbers in treatment groups (p=0.002), while osteoblast numbers were not significantly different (p=0.655). Increased osteoclasts indicate enhanced bone resorption that may impair bone homeostasis.